Synthesis, characterization, and photoluminescence properties of three two-dimensional lanthanide-containing Dawson-type polyoxometalates. Issue 36 (4th September 2019) - Wu, Hechen; Zhi, Minna; Chen, Chunli; Zhu, Yanhong; Ma, Pengtao; Wang, Jingping; Niu, Jingyang
Abstract : Three isostructural lanthanide-containing polyoxometalates with 2D network architectures were successfully obtained under hydrothermal conditions. Abstract : Three [α2 -P2 W17 O61 ] 10− -based lanthanide-containing polyoxometalates (LCPs) [N(CH3 )4 ]3 H8 Ln(H2 O)7 [Ln(H2 O)3 Ln(H2 O)4 (α2 -P2 W17 O61 )2 ]·48H2 O [Ln = La 3+ (1 ), Ce 3+ (2 ), and Pr 3+ (3 )] were successfully obtained by the reaction of a trivacant Dawson-type precursor [P2 W15 O56 ] 12− and lanthanide ions under hydrothermal conditions. The compounds1–3 were fully characterized by single-crystal X-ray diffraction and a series of analytical methods, including elemental analyses, powder X-ray diffraction (PXRD), IR spectroscopy, Raman spectroscopy, UV/vis diffuse reflectance spectroscopy, and thermogravimetric analysis (TGA). Single-crystal X-ray diffraction analyses indicated that1–3 were isostructural and exhibited a 2D network architecture through the alternative connection of [α2 -P2 W17 O61 ] 10− and lanthanide ions. The photoluminescence properties of1–3 were investigated at room temperature, and3 displayed the characteristic emissions of a Pr 3+ emitting center, indicating that POMs can transfer energy and sensitize Pr 3+ emissions. The reason for the weak emission intensity of Pr 3+ emitting ions was because the radiationless losses via a charge-transfer Pr → W state negatively affected the emission of the Pr 3+ ions in LCPs.